On the Helical Structure of Guanosine 5′-Monophosphate Formed at pH 5: Is It Left- or Right-Handed? - Wu, Gang; Kwan, Irene C. M.; Yan, Zhimin; Huang, Yining; Ye, Eric (Journal of Nucleic Acids, 2017)
Early X-ray fiber diffraction studies have established that the spontaneous gel formation of guanosine 5′-monophosphate (5′-GMP) under slightly acidic conditions (e.g., pH 5) results from self-assembly of 5′-GMP into a helical structure in which hydrogen-bonded guanine bases form a continuous helix with 15 nucleotides per 4 turns. For more than five decades, the sense of this helix is believed to be left-handed. Using multinuclear solid-state NMR and IR spectroscopic methods, we have finally determined the long-missing structural details of this helix. First, we found that this 5′-GMP helix is right-handed containing exclusive C3′-endo sugar puckers. Second, we showed that the central channel of this helix is free of Na+ ions, which is in sharp contrast to the helix formed by 5′-GMP at pH 8 where the central channel is filled with Na+ ions.